Marcellinus Comes on Emperor Anastasius A Handful of Remarks - Leszka, Mirosław J. (Studia Ceranea, 2022)
Anastasius was for Marcellinus not only a historical figure, but a ruler whose reign he was first able to observe from the perspective of his native Illyricum, and later as an inhabitant of Constantinople. The dominant influence on Marcellinus’ attitude towards Anastasius, as has already been pointed out many times, had been the Emperor’s religious policy, to which the chronicler, as a supporter of the orthodoxy, was opposed. Undoubtedly it was also not indifferent to the manner of Anastasius’ portrayal that at the time of the creation of the first Chronicle Marcellinus was either already associated with Justinian, or wanted to gain recognition in the eyes of Justin I, who after taking over the power after Anastasius’ death had taken action to reverse the negative outcomes of his predecessor’s religious policy.